Prediction of personalized speed skating results using Case-Based Reasoning - Bergman, O. A. (Norwegian University of Science and Technology, 2019)
Case-based reasoning (CBR) is an approach to problem-solving used in research for sports science in the past years. CBR is an intelligent experience-based solution solving system explained as similar problems have similar solutions, and easily adapted to various fields. In this work, we use case-based reasoning for predicting best possible finish-times for speed skaters given various external conditions.